URBAN PUBLIC TRANSPORT INNOVATION AND SERVICES: POTENTIAL PASSENGER INTENTION OF METRO JABAR TRANS - Dera Thorfiani; Ali Mohamad Rezza (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
Traffic congestion is one of the major global issues faced by big cities, including Bandung, Indonesia. According to the TomTom Traffic Index 2023, Bandung ranks 8th among the world’s most congested cities. The government has implemented the Buy The Service (BTS) programme through the Metro Jabar Trans service to improve the quality and accessibility of public transportation. Yet, passenger occupancy remains below 30%. A lack of understanding of potential customer perceptions is considered a contributing factor. Therefore, this study examined the influence of perceived service quality and innovation on potential passengers’ intention to use Metro Jabar Transit in Greater Bandung. The research employed an explanatory quantitative approach, utilising a survey of 380 respondents, which was analysed using structural Equation modelling (SEM-PLS) to examine the relationships among service perceptions, innovation, and intention to use public transport. The results indicated that the intention to use public transport is relatively high across both innovation and service. However, the number of bus stops and the availability of lines failed to meet many passengers’ expectations regarding public transport services.